“New Normal” in Learning and Teaching - Binar Kurnia Prahani; Tsung-Hui Cheng (Indonesia Approach Education, 2020)
Social distancing and physical distancing policies have been implemented in many countries for some time in the face of a COVID-19 pandemic. The new policy that has been adopted by many countries is